2015
DOI: 10.4103/1735-1995.166212
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obstructive sleep apnea and 30-day mortality among patients with pulmonary embolism

Abstract: Background:Pulmonary embolism (PE) is the most life-threatening form of venous thrombosis which causes the majority of mortalities in this category. Obstructive sleep apnea (OSA) has been indicated as one of the risk factors for thromboembolism because of hemostatic alterations. The present study was designed to seek for the relationship between OSA and 30-day mortality of patients with PE.Materials and Methods:This prospective cohort study was conducted among 137 consecutive patients referred to hospital with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Sleep apnea, a prevalent sleep disorder, has been considered as a potential cause, which yields to acute and sustained activation of the sympathetic nervous system. [ 5 6 ] In accordance with the epidemiological studies, which was implemented from 1993 to 2013, the prevalence of sleep apnea in males and females were 22% and 17%, respectively. Furthermore, these studies documented that the disease prevalence escalated with time.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Sleep apnea, a prevalent sleep disorder, has been considered as a potential cause, which yields to acute and sustained activation of the sympathetic nervous system. [ 5 6 ] In accordance with the epidemiological studies, which was implemented from 1993 to 2013, the prevalence of sleep apnea in males and females were 22% and 17%, respectively. Furthermore, these studies documented that the disease prevalence escalated with time.…”
Section: Introductionmentioning
confidence: 75%
“…[56] In accordance with the epidemiological studies, which was implemented from 1993 to 2013, the prevalence of sleep apnea in males and females were 22% and 17%, respectively. Furthermore, these studies documented that the disease prevalence escalated with time.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation could justify the findings of Joshi et al 26 , who reported prevalent OSA to be associated with lower IHM in PE patients. The same authors also suggested that OSA could lead to increased hemoglobin levels resulting from hypoxemia, which may confer a protective effect in acute PE by preventing hypoxia from worsening 14 , 26 .…”
Section: Discussionmentioning
confidence: 97%
“…OSA seems to increase the risk of PE and or recurrences 13 , yet data on the association between OSA and prognosis of PE patients are contradictory. Thus, some authors found no association between OSA and 30-day mortality in PE patients 14 , whereas others have suggested that OSA is a predictor of PE-related death 15 .…”
Section: Introductionmentioning
confidence: 99%
“…OSA is associated with the incidence of various diseases. [ 3 4 5 ] Due to the fact that it induces sleep and fatigue during the day, this syndrome increases the risk of car accidents 2–7 times. [ 6 ] OSA is a common disease that affects 2% of women and 4% of men in Western society.…”
Section: Introductionmentioning
confidence: 99%